2006
DOI: 10.1021/jp0559229
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of Migration Energy of Lithium Ions in Halides and Chalcogenides

Abstract: Migration of Li+ ions via the vacancy mechanism in LiX (X = F, Cl, Br, and I) with the rocksalt and hypothetical zinc blende structures and Li2X (X = O, S, Se, and Te) with the antifluorite structure has been investigated using first-principles projector augmented wave calculations with the generalized gradient approximation. The migration paths and energies, determined by the nudged-elastic-band method, are discussed on the basis of two idealized models: the rigid-sphere and charged-sphere models. The traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…Then, the value of energy barrier of the diffusion path increases on going from the first to the second stage of path 1a. These remarks are similar to those employed in the Li mobility in Li x CoO 2 by Van der Ven et al 36 and lithium halides by Kishida et al 27 Path 1b presents an opposite trend with regards to path 1a: the first stage presents a barrier height of 4.40 eV and the jumping Li ion overlaps significantly with neighboring oxygen counterions while it passes through, resulting in a significant energy barrier. This structural hindrance is avoided along the second stage since Li ion moves through the center of the triangle made by the three neighboring oxygen anions.…”
Section: At Composition X = 0250supporting
confidence: 83%
“…Then, the value of energy barrier of the diffusion path increases on going from the first to the second stage of path 1a. These remarks are similar to those employed in the Li mobility in Li x CoO 2 by Van der Ven et al 36 and lithium halides by Kishida et al 27 Path 1b presents an opposite trend with regards to path 1a: the first stage presents a barrier height of 4.40 eV and the jumping Li ion overlaps significantly with neighboring oxygen counterions while it passes through, resulting in a significant energy barrier. This structural hindrance is avoided along the second stage since Li ion moves through the center of the triangle made by the three neighboring oxygen anions.…”
Section: At Composition X = 0250supporting
confidence: 83%
“…As shown in the figure, formation energies for Figure 2(b)), which supports the explanation proposed by Delmas et al [45] We infer that the Coulombic interactions are the main reason for the large difference in the migration profile between the bulk and interfacial alkali ion hopping, as observed in spinel compounds. [46] In the bulk hopping mechanism, the energy maximum is located at the tetrahedral vacancy, where the short-range repulsive effect [25,26] is smaller owing to the overlap of the electron clouds of the hopping ion and surrounding oxide ions ( Figure 2 [18]. Note that net volumetric Li transportation performance is smaller than above rate difference (~7600), since fast migration only occur at the interface.…”
Section: Methodsmentioning
confidence: 98%
“…In particular, the ionic radius of Na + is larger than that of Li + , which could increase the migration energy because of the repulsion arising from electron overlap between surrounding ions during hopping. [25,26] Zhu et al reported that the diffusion coefficient of Na + is 1-2 orders of magnitude lower than that of Li + in the olivine-type FePO 4 structure. [18] To understand the difference in the rate performance between LiFePO 4 and NaFePO 4 arising from ion and electron migration, we performed first-principles density functional theory (DFT) calculations for both compounds.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 These are in sharp contrast to the Li-ion conducting Li 2 Te envelopes that form around the Li-Pb alloy particles in PbTe electrodes. 16 Li 2 Te has been computationally predicted to be Li-ion conducting, 34 whereas Li 2 S is Li-ion insulating. In the Li 2 S-free system, dissolved polysulfide species may contaminate the electrolyte or damage the lithium counter electrode, 30 leading to the more rapid negative shift of the 0.4-0.5 V reduction peak and reduced cycling performance.…”
Section: Resultsmentioning
confidence: 99%